Prevalence of Vitamin D Deficiency among Adult Population of Isfahan City, Iran (Journal of Health, Population and Nutrition, 2011)
Determination of vitamin D status in different age-groups in a community and in different climates of a country is necessary and has important implications for general health. The study was conducted to determine the prevalence of vitamin D deficiency among the adult population of Isfahan, a centrallylocated city in Iran. In this cross-sectional study, 1,111 healthy people-243 men and 868 women-aged 41.4 (mean 14 and range 20-80) years, who attended a single-consultation outpatient clinic, were selected. Serum 25-hydroxy vitamin D (25-OHD), parathyroid hormone (PTH), calcium and phosphorus concentrations were measured. Mild, moderate and severe vitamin D deficiencies were defined as 25-OHD values of 20-30 ng/mL, 10-20 ng/mL, and